Gulf Stream separation in numerical ocean models - Chassignet, E; Marshall, D (American Geophysical Union, 2008)
This chapter summarizes our present knowledge of Gulf Stream separation in numerical ocean models. High horizontal resolution ocean numerical models are now capable of simulating quite realistically the separation and path of the Gulf Stream, and significant advances have been made in the last decade in our understanding of western boundary current separation. However, the Gulf Stream separation in numerical models continues to be a challenge because it remains very sensitive to the choices made for subgrid scale parameterizations.